2006
DOI: 10.1038/sj.jcbfm.9600420
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Gene Transfer of Soluble Flt-1 Protects against Brain Ischemia with Marked Attenuation of Blood—Brain Barrier Permeability

Abstract: Brain edema is a major and often mortal complication of brain ischemia. Vascular endothelial growth factor (VEGF) is also known as a potent vascular permeability factor and may play detrimental roles at the acute stage of brain infarction. Our goal in this study was to explore protective effects of gene transfer of soluble flt-1 (sFlt-1), a natural inhibitor of VEGF, on focal brain ischemia. Adenoviral vector encoding sFlt-1 or b-galactosidase as control was injected into the lateral ventricle 90 mins after ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…These findings suggest the involvement of astrocytic ET B receptors in the production of MMPs and VEGF in brain pathologies. Because inhibition of MMPs and VEGF signals prevented the elevated vascular permeability, expressions of these factors are likely pathogenic for vasogenic brain edema (24,25). The production of brain ETs increases in the acute phases of brain insults (3).…”
Section: Production Of Vascular Permeability Factorsmentioning
confidence: 99%
“…These findings suggest the involvement of astrocytic ET B receptors in the production of MMPs and VEGF in brain pathologies. Because inhibition of MMPs and VEGF signals prevented the elevated vascular permeability, expressions of these factors are likely pathogenic for vasogenic brain edema (24,25). The production of brain ETs increases in the acute phases of brain insults (3).…”
Section: Production Of Vascular Permeability Factorsmentioning
confidence: 99%
“…23 In addition, inhibition of FLT-1 reduced brain edema after cerebral ischemia in rats, which may be associated with the protection of blood-brain barrier permeability and induction of macrophage/monocyte infiltration. 25 Interestingly, other groups found that FLK-1 and FLT-1 expression increased from day 1 to day 14 following acute spinal cord contusion injury in rats without any treatment. 26 Whereas blocking FLT-1 decreased the infiltration of inflammatory cells, blocking FLK-1 increased neuronal apoptosis and worsened the functional recovery after spinal cord injury, which indicates that FLK-1 plays a crucial neuroprotective role in spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes causes tremendous edema due to several factors including enhanced protein kinase C activation and higher oxidative stress [68]. Similarly, hypertension is associated with increased vascular endothelial growth (VEGF) and oxidative stress that can increase both hemorrhage and edema [70,71]. Thus, agents on board that inhibit these processes prior to recanalization with ET or IA delivery of these agents during ET (see below) could be effective at preventing reperfusion injury.…”
Section: Targeting Recanalization and Reperfusion As A Neuroprotectivmentioning
confidence: 99%